GIGANTEA Is a Negative Regulator of Abscisic Acid Transcriptional Responses and Sensitivity in Arabidopsis. (21st July 2022) - Siemiatkowska, Beata; Chiara, Matteo; Badiger, Bhaskara G; Riboni, Matteo; D'Avila, Francesca; Braga, Daniele; Salem, Mohamed Abd Allah; Martignago, Damiano; Colanero, Sara; Galbiati, Massimo; Giavalisco, Patrick; Tonelli, Chiara; et al.
Abstract: Transcriptional reprogramming plays a key role in drought stress responses, preceding the onset of morphological and physiological acclimation. The best-characterized signal regulating gene expression in response to drought is the phytohormone abscisic acid (ABA). ABA-regulated gene expression, biosynthesis and signaling are highly organized in a diurnal cycle, so that ABA-regulated physiological traits occur at the appropriate time of day. The mechanisms that underpin such diel oscillations in ABA signals are poorly characterized. Here we uncover GIGANTEA (GI ) as a key gatekeeper of ABA-regulated transcriptional and physiological responses. Time-resolved gene expression profiling by RNA sequencing under different irrigation scenarios indicates that gi mutants produce an exaggerated ABA response, despite accumulating wild-type levels of ABA. Comparisons with ABA-deficient mutants confirm the role of GI in controlling ABA-regulated genes, and the analysis of leaf temperature, a read-out for transpiration, supports a role for GI in the control of ABA-regulated physiological processes. Promoter regions of GI/ABA-regulated transcripts are directly targeted by different classes of transcription factors (TFs), especially PHYTOCHROME-INTERACTING FACTOR and -BINDING FACTOR, together with GI itself. We propose a model whereby diel changes in GI control oscillations in ABA responses. Peak GI accumulation at midday contributes to establishing a phase of reduced ABA sensitivity and related physiological responses, by gating DNA binding or function of different classes of TFs that cooperate or compete with GI at target regions.